Surface Tension Studies on the Micellization of Cetyltrimethylammonium Bromide in Presence and Absence of KCL and NaCl in Aqueous Media at Room Temperature - Jha, Kabita; Bhattarai, Ajaya; Chatterjee, Sujeet Kumar (BIBECHANA, 2013)
NOTE: on 27th May 2014 in the abstract, the sentence "The surface tension of cetyltrimethylammonium bromide is found less in presence of KCl than NaCl in aqueous media" was changed to read "The surface tension of cetyltrimethylammonium bromide is found more in presence of KCl than NaCl in aqueous media." In the Conclusion (p.56) the sentence "The surface tension of cetyltrimethylammonium bromide is found less in presence of KCl than NaCl in aqueous media." was changed to read "The surface tension of cetyltrimethylammonium bromide is found more in presence of KCl than NaCl in aqueous media." Precise measurements on Surface tension of cetyltrimethylammonium bromide in presence and in absence of KCl and NaCl in aqueous media are reported. The results showed a sharp decrease in surface tension with increase in concentration of cetyltrimethylammonium bromide and then almost constant value of surface tension was observed. Also, the surface tension decreases with addition of salts. The surface tension of cetyltrimethylammonium bromide is found less in presence of KCl than NaCl in aqueous media. In presence of monovalent salts, the critical micelle concentration (cmc) value decreases which is explained on the basis of the orientation of the surfactant and reduction of the free energy of the surface, thus decreasing surface tension. The graphs of surface tension versus concentration are used in determining the critical micelle concentration (cmc). BIBECHANA 10 (2014) 52-57 DOI: http://dx.doi.org/10.3126/bibechana.v10i0.9311